P027 Challenges and opportunities in embedding quality data into routine clinical practice using electronic health record systems. (23rd April 2022) - Bouraoui, Aicha; Fisher, Corinne; Sen, Debajit
Abstract: Background/Aims: The emergence of the electronic health record system (EHRS) creates opportunities for standardising clinical data which can be used for service improvement and research. However, there are also challenges related to EHRS use particularly with respect to data quality and availability. In this project, our goal is to enhance the use of EHRS to enable timely access to reliable high quality clinical data which can be used for research and Quality Improvement. We aimed to improve the entry of structured clinical data starting with problem list, medication list and core outcome variables by 70% within 12 months. Methods: We audited our current practice and developed an improvement strategy to incorporate standardized documentation into our adolescent and young adult (AYA) rheumatology clinics. We initially extracted a baseline report for AYA patients to establish our baseline data quality and availability. We also compared structured data to narrative data. Then we organised meetings to develop a shared understanding of the challenges. Subsequent departmental meetings were organised to prioritise and then agree on actions which were summarised in a driver diagram. Then we ran 5 cycles of change and measured data over time including the weekly proportion of clinic encounters using standardised problem lists, medication lists, core outcomes variables. We also measured the use of Smart tools built within our EHRS. Smart-Tools are processes that enable efficiency through easier ordering, navigation and documentation in an EHRS. Using the patient interface 'MyCare', we engaged with our patients to encourage them to prepare for their appointment including updating their medication list and completing health questionnaires. Results: Initial audit comparing structured and narrative data, revealed poor quality data with 50% of problem lists documented in a structured manner. Of those, 20% were not entered correctly. 70% of medication lists were entered in a non-structured manner. 80% of those with structured medication lists were entered inaccurately. There was no structured documentation of core outcomes variables or joint examination in all encounters which was also inconsistently entered in the free text. Over the last 12 months, 5 cycles of change were implemented testing a number of interventions including developing clinic encounters templates and smart tools within EHRS. The weekly entry of structured problem list improved from 50% to 98%. The Smart-Phrase use and AYA template weekly use rate improved from 0% to 70% and the entry of core outcome variables has improved from 0% to 30% of cases. Conclusion: This project supports the feasibility of implementing standardized data into routine clinical practice that can be used for research and service improvement. This has created an opportunity to improve data quality and accuracy. Most importantly, this work has facilitated a standardisation of clinical practice and better engagement between clinicians and patients. Disclosure: A. Bouraoui: None. C. Fisher: None. D. Sen: None.